Вы находитесь на странице: 1из 16

Section 7.

1 Periodic Functions 151


Solutions to Exercises 7.1
1. (a) cos x has period 2. (b) cos x has period T =
2

= 2. (c) cos
2
3
x has period
T =
2
2/3
= 3. (d) cos x has period 2, cos 2x has period , 2, 3,

.. A common period of cos x


and cos 2x is 2. So cos x + cos 2x has period 2.
5. The function is periodic with period 1. To describe it, we use any interval of length one period.
Let us use the interval [0, 1). On that interval, the function is given by f(x) = x. Thus, the complete
description of the function is
f(x) =
_
x if 0 x < 1,
f(x + 1) otherwise.
9. (a) Suppose that f and g are T-periodic. Then f(x + T) g(x + T) = f(x) g(x), and so f g is
T periodic. Similarly,
f(x + T)
g(x + T)
=
f(x)
g(x)
,
and so f/g is T periodic.
(b) Suppose that f is T-periodic and let h(x) = f(x/a). Then
h(x + aT) = f
_
x + aT
a
_
= f
_
x
a
+ T
_
= f
_
x
a
_
(because f is T-periodic)
= h(x).
Thus h has period aT. Replacing a by 1/a, we nd that the function f(ax) has period T/a.
(c) Suppose that f is T-periodic. Then g(f(x + T)) = g(f(x)), and so g(f(x)) is also T-periodic.
13. We have
_
/2
/2
f(x) dx =
_
/2
0
1 dx = /2.
17. By Exercise 16, F is 2 periodic, because
_
2
0
f(t) dt = 0 (this is clear from the graph of f). So
it is enough to describe F on any interval of length 2. For 0 < x < 2, we have
F(x) =
_
x
0
(1 t) dt = t
t
2
2

x
0
= x
x
2
2
.
For all other x, F(x + 2) = F(x). (b) The graph of F over the interval [0, 2] consists of the arch of
a parabola looking down, with zeros at 0 and 2. Since F is 2-periodic, the graph is repeated over
and over.
Fourier Series
Solutions to Exercises 7.2
1. The graph of the Fourier series is identical to the graph of the function, except at the points of
discontinuity where the Fourier series is equal to the average of the function at these points, which
is
1
2
.
5. We compute the Fourier coecients using he Euler formulas. Let us rst note that since
f(x) = |x| is an even function on the interval < x < , the product f(x) sin nx is an odd
function. So
b
n
=
1

odd function
..
|x| sinnx dx = 0,
because the integral of an odd function over a symmetric interval is 0. For the other coecients, we
have
a
0
=
1
2
_

f(x) dx =
1
2
_

|x| dx
= =
1
2
_
0

(x) dx +
1
2
_

0
xdx
=
1

_

0
xdx =
1
2
x
2

0
=

2
.
In computing a
n
(n 1), we will need the formula
_
xcos axdx =
cos(a x)
a
2
+
x sin(a x)
a
+ C (a = 0),
which can be derived using integration by parts. We have, for n 1,
a
n
=
1

f(x) cos nxdx =


1

|x| cos nxdx


=
2

_

0
xcos nxdx
=
2

_
x
n
sin nx +
1
n
2
cos nx
_

0
=
2

_
(1)
n
n
2

1
n
2
_
=
2
n
2
_
(1)
n
1

=
_
0 if n is even

4
n
2
if n is odd.
Thus, the Fourier series is

2

4

k=0
1
(2k + 1)
2
cos(2k + 1)x.
Section 7.2 Fourier Series 153
s n_, x_ : Pi 2 4 Pi Sum 1 2 k 1 ^2 Cos 2 k 1 x , k, 0, n
partialsums Table s n, x , n, 1, 7 ;
f x_ x 2 Pi Floor x Pi 2 Pi
g x_ Abs f x
Plot g x , x, 3 Pi, 3 Pi
Plot Evaluate g x , partialsums , x, 2 Pi, 2 Pi
The function g(x) = | x |
and its periodic extension
Partial sums of
the Fourier series. Since we are
summing over the odd integers,
when n = 7, we are actually summing
the 15th partial sum.
9. Just some hints:
(1) f is even, so all the b
n
s are zero.
(2)
a
0
=
1

_

0
x
2
dx =

2
3
.
(3) Establish the identity
_
x
2
cos(ax) dx =
2 x cos(a x)
a
2
+
_
2 + a
2
x
2
_
sin(a x)
a
3
+ C (a = 0),
using integration by parts.
13. You can compute directly as we did in Example 1, or you can use the result of Example 1 as
follows. Rename the function in Example 1 g(x). By comparing graphs, note that f(x) = 2g(x+).
Now using the Fourier series of g(x) from Example, we get
f(x) = 2

n=1
sin n( + x)
n
= 2

n=1
(1)
n+1
n
sin nx.
17. (a) Setting x = in the Fourier series expansion in Exercise 9 and using the fact that the
Fourier series converges for all x to f(x), we obtain

2
= f() =

2
3
+ 4

n=1
(1)
n
n
2
cos n =

2
3
+ 4

n=1
1
n
2
,
154 Chapter 7 Fourier Series
where we have used cos n = (1)
n
. Simplifying, we nd

2
6
=

n=1
1
n
2
.
(b) Setting x =

2
in the Fourier series expansion in Exercise 13 and using the fact that the Fourier
series converges to f(x) = x for < x < , we obtain

2
= f(/2) = 2

n=1
(1)
n+1
n
sin
n
2
= 2
_
(1)
1+1
1
sin

2
+
(1)
2+1
2
sin
2
2
+
(1)
3+1
3
sin
3
2
+ +
(1)
4+1
4
sin
4
4
+
_
= 2
_
1 + 0 +
1
3
(1) + +0 +
_
= 2
_
1
1
3
+
_
.
Dividing by 2 both sides, we get the desired identity.
21. We simply repeat the solution of Example 6, making some obvious simplications. The idea is
to realize that the function
f() =
1
3 + cos
is the restriction to the unit circle of a function that is analytic on the unit circle. This function
has a Laurent series expansion, that, when restricted to the unit circle, gives the Fourier series of f.
Write cos =
z+z
1
2
, where z = e
i
. Then
1
3 + cos
=
1
3 +
z+z
1
2
=
2z
z
2
+ 6z + 1
= g(z).
We have
z
2
+ 6z + 1 = (z z
1
)(z z
2
) wherez
1
= 3

8 and z
2
= 3 +

8.
Since |z
2
| < 1 < |z
1
|, the function g(z) is analytic on the annulus |z
2
| < |z| < |z
1
|, that contains the
unit circle. We next nd the Laurent series expansion of g in that annulus. The computation is not
straightforward, but it is done in complete detail in Example 6. I will simply recall the result of this
example (but you should go over the details leading to the cited result). We have, in the annulus
|z
2
| < |z| < |z
1
|, (take a = 3 and z
1
and z
2
as previously)
2z
z
2
+ 6z + 1
=
1

9 1
_
1 +

n=1
z
n
2
_
z
n
+
1
z
n
_
_
=
1

8
_
1 +

n=1
_
3 +

8
_
n
_
z
n
+
1
z
n
_
_
Now set z = e
i
(which is a complex number in the domain of the Laurent series), then
1
3 + cos
=
2z
z
2
+ 6z + 1
=
1

8
_
1 +

n=1
_
3 +

8
_
n _
e
in
+ e
in
_
_
=
1

8
_
1 + 2

n=1
_
3 +

8
_
n
cos n
_
,
Section 7.2 Fourier Series 155
which is the desired Fourier series.
25. The Fourier series in Example 6 is valid for all . Replacing by in the Fourier series
of Example 6, we obtain the desired Fourier series, since cos( ) = cos and cos[n( )] =
(1)
n
cos n.
156 Chapter 7 Fourier Series
Solutions to Exercises 7.3
1. (a) and (b) Since f is odd, all the a
n
s are zero and
b
n
=
2
p
_
p
0
sin
n
p
dx
=
2
n
cos
n
p

0
=
2
n
_
(1)
n
1

=
_
0 if n is even,
4
n
if n is odd.
Thus the Fourier series is
4

k=0
1
(2k + 1)
sin
(2k + 1)
p
x. At the points of discontinuity, the Fourier
series converges to the average value of the function. In this case, the average value is 0 (as can be
seen from the graph.
5. (a) and (b) The function is even. It is also continuous for all x. All the b
n
s are 0. Also, by
computing the area between the graph of f and the x-axis, from x = 0 to x = p, we see that a
0
= 0.
Now, using integration by parts, we obtain
a
n
=
2
p
_
p
0

_
2c
p
_
(x p/2) cos
n
p
xdx =
4c
p
2
_
p
0
u
..
(x p/2)
v

..
cos
n
p
x dx
=
4c
p
2
_

_
=0
..
p
n
(x p/2) sin
n
p
x

p
x=0

p
n
_
p
0
sin
n
p
xdx
_

_
=
4c
p
2
p
2
n
2

2
cos
n
p
x

p
x=0
=
4c
n
2

2
(1 cos n)
=
_
0 if n is even,
8c
n
2

2
if n is odd.
Thus the Fourier series is
f(x) =
8c

k=0
cos
_
(2k + 1)

p
x
_
(2k + 1)
2
.
9. The function is even; so all the b
n
s are 0,
a
0
=
1
p
_
p
0
e
cx
dx =
1
cp
e
cx

p
0
=
1 e
cp
cp
;
and with the help of the integral formula from Exercise 15, Section 2.2, for n 1,
a
n
=
2
p
_
p
0
e
cx
cos
nx
p
dx
=
2
p
1
n
2

2
+ p
2
c
2
_
npe
cx
sin
nx
p
p
2
ce
cx
cos
nx
p
_

p
0
=
2pc
n
2

2
+ p
2
c
2
_
1 (1)
n
e
cp

.
Thus the Fourier series is
1
pc
(1 e
cp
) + 2cp

n=1
1
c
2
p
2
+ (n)
2
(1 e
cp
(1)
n
) cos(
n
p
x) .
Section 7.3 Fourier Series of Functions with Arbitrary Periods 157
13. Take p = 1 in Exercise 1, call the function in Exercise 1 f(x) and the function in this exercise
g(x). By comparing graphs, we see that
g(x) =
1
2
(1 + f(x)) .
Thus the Fourier series of g is
1
2
_
1 +
4

k=0
1
(2k + 1)
sin(2k + 1)x
_
=
1
2
+
2

k=0
1
(2k + 1)
sin(2k + 1)x.
f x_ Which x 0, 0, 0 x 1, 1, x 1, 0
s n_, x_ 1 2 2 Pi Sum 1 2 k 1 Sin 2 k 1 Pi x , k, 0, n ;
Plot Evaluate f x , s 20, x , x, 1, 1
Which x 0, 0, 0 x 1, 1, x 1, 0
The 41st partial sum of the Fourier series
and the function on the interval (-1, 1).
17. (a) Take x = 0 in the Fourier series of Exercise 4 and get
0 =
p
2
3

4p
2

n=1
(1)
n1
n
2


2
12
=

n=1
(1)
n1
n
2
.
(b) Take x = p in the Fourier series of Exercise 4 and get
p
2
=
p
2
3

4p
2

n=1
(1)
n1
(1)
n
n
2


2
6
=

n=1
1
n
2
.
Summing over the even and odd integers separately, we get

2
6
=

n=1
1
n
2
=

k=0
1
(2k + 1)
2
+

k=1
1
(2k)
2
.
But

k=1
1
(2k)
2
=
1
4

k=1
1
k
2
=
1
4

2
6
. So

2
6
=

k=0
1
(2k + 1)
2
+

2
24

k=0
1
(2k + 1)
2
=

2
6


2
24
=

2
8
.
158 Chapter 7 Fourier Series
21. From the graph, we have
f(x) =
_
1 x if 1 < x < 0,
1 + x if 0 < x < 1.
So
f(x) =
_
1 x if 1 < x < 0,
1 + x if 0 < x < 1;
hence
f
e
(x) =
f(x) + f(x)
2
=
_
x if 1 < x < 0,
x if 0 < x < 1,
and
f
o
(x) =
f(x) f(x)
2
=
_
1 if 1 < x < 0,
1 if 0 < x < 1.
Note that, f
e
(x) = |x| for 1 < x < 1. The Fourier series of f is the sum of the Fourier series of f
e
and f
o
. From Example 1 with p = 1,
f
e
(x) =
1
2

4

k=0
1
(2k + 1)
2
cos[(2k + 1)x].
From Exercise 1 with p = 1,
f
o
(x) =
4

k=0
1
2k + 1
sin[(2k + 1)x].
Hence
f(x) =
1
2
+
4

k=0
_

cos[(2k + 1)x]
(2k + 1)
2
+
sin[(2k + 1)x]
2k + 1
_
.
25. Since f is 2p-periodic and continuous, we have f(p) = f(p + 2p) = f(p). Now
a

0
=
1
2p
_
p
p
f

(x) dx =
1
2p
f(x)

p
p
=
1
2p
(f(p) f(p)) = 0.
Integrating by parts, we get
a

n
=
1
p
_
p
p
f

(x) cos
nx
p
dx
=
1
p
=0
..
f(x) cos
nx
p

p
p
+
n
p
bn
..
1
p
_
p
p
f(x) sin
nx
p
dx
=
n
p
b
n
.
Similarly,
b

n
=
1
p
_
p
p
f

(x) sin
nx
p
dx
=
1
p
=0
..
f(x) sin
nx
p

p
p

n
p
an
..
1
p
_
p
p
f(x) cos
nx
p
dx
=
n
p
a
n
.
Section 7.3 Fourier Series of Functions with Arbitrary Periods 159
29. The function in Exercise 8 is piecewise smooth and continuous, with a piecewise smooth
derivative. We have
f

(x) =
_
_
_

c
d
if 0 < x < d,
0 if d < |x| < p,
c
d
if d < x < 0.
The Fourier series of f

is obtained by dierentiating term by term the Fourier series of f (by


Exercise 26). Now the function in this exercise is obtained by multiplying f

(x) by
d
c
. So the
desired Fourier series is

d
c
f

(x) =
d
c
2cp
d
2

n=1
1 cos
dn
p
n
2
_

n
p
_
sin
n
p
x =
2

n=1
1 cos
dn
p
n
sin
n
p
x.
33. The function F(x) is continuous and piecewise smooth with F

(x) = f(x) at all the points


where f is continuous (see Exercise 25, Section 2.1). So, by Exercise 26, if we dierentiate the
Fourier series of F, we get the Fourier series of f. Write
F(x) = A
0
+

n=1
_
A
n
cos
n
p
x + B
n
sin
n
p
x
_
and
f(x) =

n=1
_
a
n
cos
n
p
x + b
n
sin
n
p
x
_
.
Note that the a
0
term of the Fourier series of f is 0 because by assumption
_
2p
0
f(x) dx = 0.
Dierentiate the series for F and equate it to the series for f and get

n=1
_
A
n
n
p
sin
n
p
x +
n
p
B
n
cos
n
p
x
_
=

n=1
_
a
n
cos
n
p
x + b
n
sin
n
p
x
_
.
Equate the nth Fourier coecients and get
A
n
n
p
= b
n
A
n
=
p
n
b
n
;
B
n
n
p
= a
n
B
n
=
p
n
a
n
.
This derives the nth Fourier coecients of F for n 1. To get A
0
, note that F(0) = 0 because of
the denition of F(x) =
_
x
0
f(t) dt. So
0 = F(0) = A
0
+

n=1
A
n
= A
0
+

n=1

p
n
b
n
;
and so A
0
=

n=1
p
n
b
n
. We thus obtained the Fourier series of F in terms of the Fourier coecients
of f; more precisely,
F(x) =
p

n=1
b
n
n
+

n=1
_

p
n
b
n
cos
n
p
x +
p
n
a
n
sin
n
p
x
_
.
The point of this result is to tell you that, in order to derive the Fourier series of F, you can integrate
the Fourier series of f term by term. Furthermore, the only assumption on f is that it is piecewise
160 Chapter 7 Fourier Series
smooth and integrates to 0 over one period (to guarantee the periodicity of F.) Indeed, if you start
with the Fourier series of f,
f(t) =

n=1
_
a
n
cos
n
p
t + b
n
sin
n
p
t
_
,
and integrate term by term, you get
F(x) =
_
x
0
f(t) dt =

n=1
_
a
n
_
x
0
cos
n
p
t dt + b
n
_
x
0
sin
n
p
t dt
_
=

n=1
_
a
n
_
p
n
_
sin
n
p
t

x
0
dt + b
n
_

p
n
_
cos
n
p
t

x
0
_
=
p

n=1
b
n
n
+

n=1
_

p
n
b
n
cos
n
p
x +
p
n
a
n
sin
n
p
x
_
,
as derived earlier. See the following exercise for an illustration.
Section 7.4 Half-Range Expansions: The Cosine and Sine Series 161
Solutions to Exercises 7.4
1. The even extension is the function that is identically 1. So the cosine Fourier series is just the
constant 1. The odd extension yields the function in Exercise 1, Section 2.3, with p = 1. So the sine
series is
4

k=0
sin((2k + 1)x)
2k + 1
.
This is also obtained by evaluating the integral in (4), which gives
b
n
= 2
_
1
0
sin(nx) dx =
2
n
cos nx

1
0
=
2
n
(1 (1)
n
).
9. We have
b
n
= 2
_
1
0
x(1 x) sin(nx) dx.
To evaluate this integral, we will use integration by parts to derive the following two formulas: for
a = 0,
_
xsin(ax) dx =
x cos(a x)
a
+
sin(a x)
a
2
+ C,
and
_
x
2
sin(ax) dx =
2 cos(a x)
a
3

x
2
cos(a x)
a
+
2 x sin(a x)
a
2
+ C.
So
_
x(1 x) sin(ax) dx
=
2 cos(a x)
a
3

x cos(a x)
a
+
x
2
cos(a x)
a
+
sin(a x)
a
2

2 x sin(a x)
a
2
+ C.
Applying the formula with a = n, we get
_
1
0
x(1 x) sin(nx) dx
=
2 cos(n x)
(n)
3

x cos(n x)
n
+
x
2
cos(n x)
n
+
sin(n x)
(n)
2

2 x sin(n x)
(n)
2

1
0
=
2 ((1)
n
1)
(n)
3

(1)
n
n
+
(1)
n
n
=
2 ((1)
n
1)
(n)
3
=
_
4
(n)
3
if n is odd,
0 if n is even.
Thus
b
n
=
_
8
(n)
3
if n is odd,
0 if n is even,
Hence the sine series in
8

k=0
sin(2k + 1)x
(2k + 1)
3
.
162 Chapter 7 Fourier Series
b k_ 8 Pi^3 1 2 k 1 ^3;
ss n_, x_ : Sum b k Sin 2 k 1 Pi x , k, 0, n ;
partialsineseries Table ss n, x , n, 1, 5 ;
f x_ x 1 x
Plot Evaluate partialsineseries, f x , x, 0, 1
0.2 0.4 0.6 0.8 1
0.05
0.1
0.15
0.2
0.25
Perfect!
13. We have
sin xcos x =
1
2
sin 2x.
This yields the desired 2-periodic sine series expansion.
17. (b) Sine series expansion:
b
n
=
2
p
_
a
0
h
a
xsin
nx
p
dx +
2
p
_
p
a
h
a p
(x p) sin
nx
p
dx
=
2h
ap
_
x
p
n
cos
nx
p

a
0
+
p
n
_
a
0
cos
nx
p
dx
_
+
2h
(a p)p
_
(x p)
(p)
n
cos(
n x
p
)

p
a
+
_
p
a
p
n
cos
n x
p
dx
_
=
2h
pa
_
ap
n
cos
na
p
+
p
2
(n)
2
sin
na
p
_
+
2h
(a p)p
_
p
n
(a p) cos
na
p

p
2
(n)
2
sin
na
p
_
=
2hp
(n)
2
sin
na
p
_
1
a

1
a p

=
2hp
2
(n)
2
(p a)a
sin
na
p
.
Hence, we obtain the given Fourier series.
Section 7.5 Complex Form of Fourier Series 163
Solutions to Exercises 7.5
1. From Example 1, for a = 0, i, 2i, 3i, . . .,
e
ax
=
sinh a

n=
(1)
n
a in
e
inx
( < x < );
consequently,
e
ax
=
sinh a

n=
(1)
n
a + in
e
inx
( < x < ),
and so, for < x < ,
cosh ax =
e
ax
+ e
ax
2
=
sinh a
2

n=
(1)
n
_
1
a + in
+
1
a in
_
e
inx
=
a sinh a

n=
(1)
n
n
2
+ a
2
e
inx
.
2. From Example 1, for a = 0, i, 2i, 3i, . . .,
e
ax
=
sinh a

n=
(1)
n
a in
e
inx
( < x < );
consequently,
e
ax
=
sinh a

n=
(1)
n
a + in
e
inx
( < x < ),
and so, for < x < ,
sinh ax =
e
ax
e
ax
2
=
sinh a
2

n=
(1)
n
_
1
a in

1
a + in
_
e
inx
=
i sinh a

n=
(1)
n
n
n
2
+ a
2
e
inx
.
5. Use identities (1); then
cos 2x + 2 cos 3x =
e
2ix
+ e
2ix
2
+ 2
e
3ix
+ e
3ix
2
= e
3ix
+
e
2ix
2
+
e
2ix
2
+ e
3ix
.
9. If m = n then
c
m
= c
n
=
1
2
_

..
e
inx
= f(x)e
inx
dx =
1
2
_

dx = 1.
164 Chapter 7 Fourier Series
If m = n, then
c
m
=
1
2
_

e
inx
e
imx
dx =
1
2
_

e
i(nm)x
dx
=
i
2(n m)
e
i(nm)x

=
i
2(n m)
_
e
i(nm)
e
i(nm)
_
=
i
2(n m)
(cos[(n m)] cos[(n m)]) = 0.
Thus all the Fourier coecients are 0 except c
n
= n. Hence e
inx
is its own Fourier series.
(b) Because of the linearity of the Fourier coecients and by part (a), the function is its own Fourier
series.
13. (a) This is straightforward. Start with the Fourier series in Exercise 1: For a = 0, i, 2i, 3i, . . .,
and < x < , we have
cosh ax =
a sinh a

n=
(1)
n
n
2
+ a
2
e
inx
.
On the left side, we have
1
2
_

cosh
2
(ax) dx =
1

_

0
cosh(2ax) + 1
2
dx
=
1
2
_
x +
1
2a
sinh(2ax)

0
=
1
2
_
+
1
2a
sinh(2a)

.
On the right side of Parsevals identity, we have
(a sinh a)
2

n=
1
(n
2
+ a
2
)
2
.
Hence
1
2
_
+
1
2a
sinh(2a)

=
(a sinh a)
2

n=
1
(n
2
+ a
2
)
2
.
Simplifying, we get

n=
1
(n
2
+ a
2
)
2
=

2(a sinh a)
2
_
+
1
2a
sinh(2a)

.
(b) This part is similar to part (a). Start with the Fourier series of Exercise 2: For a = 0, i, 2i, 3i, . . .,
and < x < , we have
sinh ax =
i sinh a

n=
(1)
n
n
n
2
+ a
2
e
inx
.
On the left side, we have
1
2
_

sinh
2
(ax) dx =
1

_

0
cosh(2ax) 1
2
dx
=
1
2
_
x +
1
2a
sinh(2ax)

0
=
1
2
_
+
1
2a
sinh(2a)

.
Section 7.5 Complex Form of Fourier Series 165
On the right side of Parsevals identity, we have
sinh
2
a

n=
n
2
(n
2
+ a
2
)
2
.
Hence
1
2
_
+
1
2a
sinh(2a)

=
sinh
2
(a)

n=
n
2
(n
2
+ a
2
)
2
.
Simplifying, we get

n=
n
2
(n
2
+ a
2
)
2
=

2 sinh
2
(a)
_
+
1
2a
sinh(2a)

.
17. In the Taylor series
e
z
=

m=1
z
m
m!
(all z),
take z = e
i
. Then, for all ,
e
e
i
=

m=1
e
im
m!
,
which is the complex form of the Fourier series of e
e
i
= e
cos +i sin
.
21. To nd the complex Fourier coecients of f, we use (6) and the fact that the (usual) Fourier
coecients of f are a
n
= 0 for n and b
n
=
2(1)
n+1
n
(see Exercise 13, Section 7.2). Thus
c
n
=
i
2
b
n
=
i(1)
n+1
n
if n > 0 and
c
n
=
i
2
b
n
=
i(1)
n+1
n
if n < 0. Thus the Fourier coecients of f f are

1
n
2
for all n = 0.
These coecients are 4 times the coecients of the convolution that we have in Example 4. Thus
the convolution in this exercise is 4 times the function in Example 6. Thus, for x in (0, 2),
f f(x) =
1
2
_

2
3
(x )
2
_
.
25. (a) At x = , the Fourier series converges to the average of the function,
(f(+) + f())/2 =
e
a
+ e
a
2
= cosh a
166 Chapter 7 Fourier Series
(this is clear on Figure 1). Thus
cosh a =
sinh a

n=
(1)
n
a
2
+ n
2
(a + in)
=(1)
n
..
e
in
=
sinh a

n=
(a + in)
a
2
+ n
2
+
1
a
+

n=1
(1)
n
a
2
+ n
2
(a + in)e
inx
=
1
a
+
sinh a

n=1
(a in)
a
2
+ n
2
+

n=1
(a + in)
a
2
+ n
2
=
1
a
+
sinh a

n=1
2a
a
2
+ n
2
.
(b) Multiply both sides by
a
sinh a
and the desired identity follows.